Substitute x for -1 in <span> y=3x-1
</span>y = <span><span>(3) <span>(-1) -</span></span><span>1
</span></span>Solve
y = (3) (-1) -1
y = -3 - 1
y = -4
B.) -4 is your answer
<h3>2
Answers: Choice B, Choice C</h3>
The rule we use here is
If the font size is too small, then it says (a^b)/(a^c) = a^(b-c)
We subtract the exponents when dividing exponentials like this. The bases must be the same.
So this means the exponents 13 and 3 subtract to get 13-3 = 10
We either have an exponent of "13-3" or an exponent of "10" as an equivalent expression. The base stays at 2 the entire time.
Answer:
Step-by-step explanation:
We'll combine the and the on the right side.
Now, we'll subtract from both sides.
Divide both sides by .
Ta-da!
go to the link the person took and you’ll get the answer i believe.
Answer:
3) 0.30
The probability a randomly selected<em> student plays a sport</em> given they work part time = 0.30
Step-by-step explanation:
<u><em>Step(i)</em></u>:-
Given 'A' plays a sport
B work part time
Given P(A) = 0.48
P(B) = 0.40
P(A∩B) =0.12
P(A∪B)¹ =0.24
<u><em>Step(ii)</em></u>:-
By using conditional probability
and similarly
The probability a randomly selected<em> student plays a sport</em> given they work part time
Now
<u>Final answer</u>:-
The probability a randomly selected<em> student plays a sport</em> given they work part time = 0.30